2013
DOI: 10.21608/ejabf.2013.2160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental parameters on fish condition and quality in Lake Edku,Egypt

Abstract: This study was carried out between May 2011 and February 2012 in order to determine the effect of environmental parameters on physical and chemical quality of water, fish condition as well as fish quality in Lake Edku. Fish condition; lengthweight relation, condition factor and hepatosomatic index of three cichlid species (O. niloticus, O. aureus and T. zillii) were studied. Also, fish quality as heavy metals accumulation and proximate body composition for muscle tissue of these species were estimated. Physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 11 publications
2
16
3
Order By: Relevance
“…Where, station 3 was had the significantly (p > 0.05) increase than other stations of reactive phosphate are mostly because of drainage water enriched with phosphorous compounds. The concentration of all nutrients (NH4, NO2, NO3, OP4 & TP) in this study were higher than those recorded in the same lake by (Saeed, 2013;Okbah et al, 2017& El Morshedy, 2017.…”
Section: Results and Discussion Physicochemical Parameters And Nutriecontrasting
confidence: 75%
“…Where, station 3 was had the significantly (p > 0.05) increase than other stations of reactive phosphate are mostly because of drainage water enriched with phosphorous compounds. The concentration of all nutrients (NH4, NO2, NO3, OP4 & TP) in this study were higher than those recorded in the same lake by (Saeed, 2013;Okbah et al, 2017& El Morshedy, 2017.…”
Section: Results and Discussion Physicochemical Parameters And Nutriecontrasting
confidence: 75%
“…The low value (0.74 µM) was measured at site II could be attributed to two factors; the first is the absence of dissolved oxygen that inhibits the rate of chemical oxidation of ammonia and the second is dissimilatory nitrate reduction to ammonium i.e. the reduction of nitrate to ammonia [35,40,41]. On other hand the high value of 36.74µM was measured at site VIII could be attributed to high amounts of organic fertilizers, industrial discharges [42,43], and also may be due to the absence of phytoplankton that inhibits the uptake of NO 3 by phytoplankton.…”
Section: Nutrient Saltsmentioning
confidence: 89%
“…Moreover, stepwise regression analysis revealed that 97% of pH variability could be related to DO (pH = 4.55+0.499DO+0.452OOM+0.998T. alkalinity, r = 0.97, p ≤ 0.001) [35]. Moderately oxygenated seawater samples are mainly related to some other environmental factors.…”
Section: Physicochemical Parametersmentioning
confidence: 97%
See 2 more Smart Citations